EFFECT OF PROSTAGLANDIN F2a AND OXYTOCIN ON SEMINAL CHARACTERISTICS IN CHHOTTANAGPURI RAMS - KUMAR SINGH, AMIT RANJAN; KUMAR JHA, DILIP; SINGH, M P; SINGH, SRINIWAS (The Indian Journal of Animal Reproduction, 2023)
A study was conducted on chhottanagpuri ram to see the effect of oxytocin and prostaglandin F2a on seminal characteristics. Immediately after semen collection, all the semen samples were brought to the laboratory and were evaluated for colour, ejaculate volume, mass activity, pH, sperm concentration, live sperm percentage and abnormal sperm percentage. There was significant (p<0.01) increase in ejaculate volume, sperm concentration and sperm head abnormalities after prostaglandin administration. It was also found that oxytocin administration increases ejaculate volume, mass activities and sperm concentration of semen significantly (p<0.01) during this study.